Diet of phyllostomid bats of Kosñipata Valley, San Pedro, Cusco - Peru - Maguiña, Rossana (2012)
In this study had been evaluated the diet of phyllostomids bats of the montane forest of the Kosñipata Valley (San Pedro, Cusco). The species of bats evaluated belong to the genus Carollia, Sturnira and Anoura. The diet was evaluated regarding the presence of pollen and seeds in fecal samples. Also, it was analyzed the importance of the plants consumed, the food niche breath and the food niche overlap. The results showed that the diet of the bats is mostly compounded of fruit and nectar-pollen of the plants. The principal resources registered belong to the genus Piper (registered in 23,08% of the samples), Cecropia (in 21,15%) and Abutilon (in 13,46%), which was the most important resources for the community of bats evaluated. The food niche breath of the six species analyzed showed that they are specialist in their diet in the study zone. The highest level of food niche overlap occurs between the species C. brevicauda, C. perspicillata and S. erythromos.